Cutaneous adverse effects of hormonal adjuvant therapy for breast cancer: A case of localised urticarial vasculitis following anastrozole therapy and a review of the literature. (2nd December 2013) - Bock, Vanessa L.; Friedlander, Michael; Waring, Dale; Kossard, Steven; Wood, Glenda K.
Abstract Hormonal therapy with either tamoxifen or aromatase inhibitors is commonly used to treat women with breast cancer in both the adjuvant and recurrent disease setting. Cutaneous adverse reactions to these drugs have been rarely reported in the literature. We report an unusual case of urticarial vasculitis following the aromatase inhibitor anastrozole that localised to the unilateral trunk and mastectomy scar, and review the literature on the cutaneous adverse effects of hormonal therapy for breast cancer.